2007
DOI: 10.1104/pp.107.097246
|View full text |Cite
|
Sign up to set email alerts
|

The Mi-1-Mediated Pest Resistance Requires Hsp90 and Sgt1  

Abstract: The tomato (Solanum lycopersicum) Mi-1 gene encodes a protein with putative coiled-coil nucleotide-binding site and leucine-rich repeat motifs. Mi-1 confers resistance to root-knot nematodes (Meloidogyne spp.), potato aphids (Macrosiphum euphorbiae), and sweet potato whitefly (Bemisia tabaci). To identify genes required in the Mi-1-mediated resistance to nematodes and aphids, we used tobacco rattle virus (TRV)-based virus-induced gene silencing (VIGS) to repress candidate genes and assay for nematode and aphid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
119
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(127 citation statements)
references
References 47 publications
8
119
0
Order By: Relevance
“…HSP90 is required for Mi resistance in tomato (Bhattarai et al, 2007), and Hsc70 is involved in tomato responses to Ralstonia solanacearum (Byth et al, 2001). Most of the other genes induced by infection of MG or RR fruit have unknown functions.…”
Section: B Cinerea-inducible Gene Expression Changesmentioning
confidence: 99%
“…HSP90 is required for Mi resistance in tomato (Bhattarai et al, 2007), and Hsc70 is involved in tomato responses to Ralstonia solanacearum (Byth et al, 2001). Most of the other genes induced by infection of MG or RR fruit have unknown functions.…”
Section: B Cinerea-inducible Gene Expression Changesmentioning
confidence: 99%
“…Zarate et al (2007)). The only R (resistance) gene in tomato which has been shown to interact with any whitefly species to date is the Mi-1.2 gene (which encodes a protein with putative coiled-coil nucleotide-binding site and leucine-rich repeat motifs; Bhattarai et al (2007)) which has been shown to confer resistance to B. tabaci in tomato, as well as the root-knot nematode and potato aphid (Nombela et al 2003). RNA transcripts of jasmonate and ethylene-responsive pathogenesis-related (PR) proteins, such as the glucanase GluB, the chitinase Chi9 and Pathogenesis-related protein-1, have been shown to accumulate in infested tomato leaves in response to feeding by B. tabaci and T. vaporariorum nymphs, indicating a role for these proteins in tomato whitefly resistance (Puthoff et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The function of these proteins in disease resistance responses have been extensively investigated previously using mutant analyses Chandra-Shekara et al, 2004;Hubert el al., 2003;Lu et al, 2003;Shirasu et al, 1999;Takahashi et al, 2003) and by virus induced gene silencing (VIGS) analyses in several plant species (Bhattarai et al, 2007;de la Fuente van Bentem et al, 2005;Leister et al, 2005;Liu et al, 2004;Scofield et al, 2005). The data from these studies revealed differing specificities for these proteins in diverse NB-LRR-mediated resistance responses.…”
Section: Discussionmentioning
confidence: 98%